Envueltas en el Niqab y mirando hacia el futuro. Género, tolerancia y multiculturalismo - Pérez Bernal, Marian (CUADERNOS KÓRE, 2012)
In today’s Europe it is a basic citizen concern and policy to find ways that allow the coexistence of people coming from different cultures. In this paper, based on the analysis of different policies concerning the use of the Islamic headscarf, we analyse the potential danger multiculturalism might bear for the rights of women. We also advocate a new form to manage multiculturalism recovering the ideals of the Enlightenment.